THE DEVELOPMENT OF ENGLISH MATERIALS FOR THE ELEVENTH GRADERS OF BUSINESS MARKETING PROGRAM - Al Dikstaal, Hanan Shadily (RETAIN, 2021)
In Indonesia, ESP is appropriate to be taught at vocational high schools since the students at vocational high schools are taught to develop specific skills based on their major. However, most English teachers of vocational high schools in Indonesia have not taught ESP. There were four objectives of this study. The first one was to identify the need of the eleventh grade students of Business Marketing Program in learning English. The second one was to identify the contents that should be included in English materials for the eleventh grade students of Business Marketing Program. The third one was to develop the appropriate English materials for the eleventh grade students of Business Marketing Program. The last one was to find out the teacher’s response toward the English materials developed. The results showed that the eleventh grade students of Business Marketing needed to learn English because having English skills will help them a lot when they start to work in the future in this global competition era. As marketing students, they thought that they needed specific English materials for Business Marketing Program which contains more speaking activity. In terms of the content, they agreed that the materials should be able to develop their language skills. Therefore, they thought that they had still to learn all the language skills. However, they felt that the materials should focus more on developing their speaking skill and pronunciation since as marketing students, they are expected to be able to bargain, promote and also explain the products they are selling. In developing the materials, the researcher applied the materials adaptation method, and the result showed that according to the teacher, the materials developed were overall good and gave benefits for both teacher and students. Moreover, the teacher said that the materials have met the students’ need in learning English. Keywords: English materials development, English for Specific Purposes, students need, Business Marketing Program.